Traceability of animal meals in quail eggs using carbon and nitrogen stable isotopes - Dias Ishizuka, Adriele Nayara [UNESP]; Gonzales de Carvalho, Marco Antonio [UNESP]; Aparecido Cardoso Araujo, Robert Guaracy [UNESP]; Denadai, Juliana Celia [UNESP]; Mendes Pimenta, Guilherme Emygdio [UNESP]; Pereira Sartori, Maria Marcia [UNESP]; Costa, Vladimir Eliodoro [UNESP] (Empresa Brasil Pesq Agropec, 2020)
The objective of this work was to detect the inclusion of animal meal in Japanese quail (Coturnix coturnix japonica) diets, by analyzing eggs and their fractions (albumen and yolk) through the technique of carbon (C-13/C-12) and nitrogen (N-15/N-14) stable isotopes. Four hundred and thirty-two Japanese quails, 45-day-old females, were distributed in a completely randomized experimental design, in eight treatments: T1, strictly vegetable diet (VEG), with corn (Zea mays) and soybean (Glycine max) meal: T2, bovine meat and bone meal (BM); T3, poultry viscera meal (OM); T4, feather meal (FM); T5, BM+OM; T6, BM+FM; T7, OM+FM; and T8, BM+OM+FM. Sixteen eggs were randomly collected from each treatment - eight for whole egg analysis and eight for separate yolk and albumen analyses. To determine the turnover rate, the exponential isotope dilution model was used. The application of C and N stable isotopes allows identifying the use of animal meal in coded diets through the analysis of whole eggs and their fractions, which suggests that this technique is a promising tool for the traceability and certification of products of animal origin.
Keywords: Coturnix coturnix japonica; bovine meal; certification; feather meal; poultry viscera meal